Study of Perception of Vocational Teachers on the Use and Effectiveness of Teaching Methods in Agriculture Vocational Subject at Higher Secondary Schools of Haryana & Himachal Pradesh (INDIAN JOURNAL OF VOCATIONAL EDUCATION, 2025)
The purpose of this study was to understand the perception of vocational teachers in schools of Haryana and Himachal Pradesh regarding the use and effectiveness of teaching methods in agriculture. The sample of the study consisted of a total of 100 vocational teachers of agriculture and students from government schools of Haryana and Himachal Pradesh. A descriptive survey design was adopted for this study. The survey instruments ‘were questionnaires, which were administered to students and vocational teachers. The questionnaire for students had questions on their preferences for teaching methods on selected topics and the questionnaire for vocational teachers had questions on the extent of use and effectiveness of teaching methods in agriculture for the chosen topics.Findings showed that students of vocational subjects in agriculture in Haryana preferred practical training, field visits, presentation, and lecture method for learning the selected topics in agriculture. In Himachal Pradesh, vocational students mostly preferred fieldvisits, practical training, demonstration, and lecture method in agriculture. Further, in Haryana, although the vocational teachers perceived practical training as more effective than other teaching methods, in practice however, most of them used the lecture method for teaching a majority of the topics in agriculture. In Himachal Pradesh, practical training, lecture method, field visit, and demonstration were considered the most effective for teaching agriculture. However, while teaching the selected topics most of the vocational teachers used the lecture method. With regard to the application of teaching methods, vocational teachers of Haryana and Himachal Pradesh need to endorse the use of practical training methods, like field visits and demonstration methods, over lecture and discussion methods so as to promote experiential learning for imparting knowledge and skills to students in agriculture.